2009
DOI: 10.2119/molmed.2009.00091
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Significance of Coagulation Abnormalities in Community-Acquired Pneumonia

Abstract: Coagulation abnormalities are common in severe pneumonia and sepsis, yet little is known about the presence of coagulopathy or its significance in patients with lesser illness severity. We examined coagulation abnormalities in 939 subjects hospitalized with community-acquired pneumonia (CAP) in 28 US hospitals, hypothesizing that abnormalities would increase with illness severity and poor outcomes. We measured plasma coagulation markers (D-dimer, plasminogen activator inhibitor [PAI], antithrombin, factor IX, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
1
11

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(111 citation statements)
references
References 43 publications
6
93
1
11
Order By: Relevance
“…About 90% of inpatients with pneumonia had increased coagulation activity, marked by increased d-dimer concentrations. 25 In this study, we found d-dimer greater than 1 µg/mL is associated with fatal outcome of COVID-19. High levels of d-dimer have a reported asso ciation with 28-day mortality in patients with infection or sepsis identified in the emergency department.…”
Section: Discussionmentioning
confidence: 51%
“…About 90% of inpatients with pneumonia had increased coagulation activity, marked by increased d-dimer concentrations. 25 In this study, we found d-dimer greater than 1 µg/mL is associated with fatal outcome of COVID-19. High levels of d-dimer have a reported asso ciation with 28-day mortality in patients with infection or sepsis identified in the emergency department.…”
Section: Discussionmentioning
confidence: 51%
“…INR was elevated at day 0, and significantly decreased over time. INR improvement in patients treated with TCZ should be considered as a positive result since an elevated INR is usually associated with more severe cases of bacterial and viral pneumonia [29].…”
Section: Discussionmentioning
confidence: 99%
“…Details of the study design, eligibility criteria, and clinical definitions have been published elsewhere (2630). Briefly, we enrolled subjects >18 years old, who had a clinical and radiological diagnosis of pneumonia per criteria of Fine et al (31), and provided informed consent directly or by proxy.…”
Section: Methodsmentioning
confidence: 99%